Supporting alternative strategies for learning chemical applications of group theory - Southam, Daniel; Lewis, J. (American Chemical Society, 2013)
A group theory course for chemists was taught entirely with process oriented guided inquiry learning (POGIL) to facilitate alternative strategies for learning. Students completed a test of one aspect of visuospatial aptitude to determine their individual approaches to solving spatial tasks, and were sorted into groups for analysis on the basis of their aptitude. Affective constructs from self-determination theory relating to motivation were also assessed. Students without strong visuospatial skills found the activities more interesting and enjoyable than students who could successfully complete spatial tasks. Equally successful outcomes were observed on an assessment task, irrespective of visuospatial aptitude of the student. This illustrates that a pedagogy structured around multiple strategies for reasoning can successfully support alternative approaches to abstract concepts, such as chemical applications of group theory.